PENGARUH HERBAL COMPRES BALL TERHADAP PENURUNAN NYERI OTOT PADA LANSIA - Apriani, Miftah; Fatrin, Tiara; Wijayanti, Adhika (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2024)
ABSTRACT Muscle pain is an unpleasant emotional and sensory experience associated with the risk of actual or potential damage. The results of a direct survey at the Palembang City Regional Social Home showed that the majority of elderly people experienced muscle pain. One non-pharmacological therapy to reduce the scale of muscle pain is Herbal Compress Ball therapy, the effect of which comes from heat conduction which can increase regional blood flow to the pain area, the analgesic effect comes from herbal ingredients and aromatherapy essential oils provide a relaxing effect. This study aims to determine the effect of the Herbal Compress Ball on reducing muscle pain in the elderly. The measuring tool used is an observation sheet with a muscle pain scale used is the Wong-Baker FACES Rating Scale, divided into no pain, mild pain, moderate pain, controlled severe pain, and uncontrolled severe pain. The design of this research is an experimental one-group pre-post test design. The sampling technique is purposive sampling with a sample size of 15 respondents. Data analysis was carried out using the Wilcoxon sign rank test, and the p value = 0.000 (p < 0.05). This research shows that there is an effect of Herbal Compress Ball on reducing muscle pain in the elderly in social institutions in the Palembang city area. It is hoped that future researchers can complete this research by adding a control group and comparing the effectiveness of the Herbal Compress Ball between the intervention group and the control group.